Fabrication of porous imidazole polymerized ionic liquids with fast ion diffusing kinetics for super lithiation anode materials in lithium-ion batteries. Issue 32 (11th July 2022) - Wang, Yeji; Yang, Gege; Jiang, Fei; Qiu, Tianpei; Liu, Qian; Zhou, Le; Yang, Chaofan; Huang, Junjie; Dai, Guoliang
Abstract : Porous imidazole polymerized ionic liquids (PILs-Im) with fast Li + diffusion kinetics and numerous molecular pores have been used as anodes in lithium-ion batteries for the first time. Abstract : Porous imidazole polymerized ionic liquids (PILs-Im) with fast Li + diffusion kinetics and numerous molecular pores have been used as anodes in lithium-ion batteries for the first time. In situ FTIR, ex situ XPS and DFT calculations indicate that the N atoms in aromatic rings and methylene C react with Li + to form N–Li and C–Li bonds, realizing a specific capacity of 846.6 mA h g −1 at 100 mA g −1 with super lithiation in Li0.5 (C/N). PILs-Im also exhibit excellent cycling stability (598.7 mA h g −1 at 1.0 A g −1 ) after 500 cycles, and a superior rate capability of 165 mA h g −1 at 10 A g −1 . The excellent lithium storage performance could be attributed to the ionic skeleton allowing fast Li + diffusion, abundant micropores facilitating the filtration of liquid electrolyte, and large cross-linking system with strong endurance to the volume variation of Li + insertion. Polymerized ionic liquids give a new route to provide traditional electrodes with a high Li + diffusion coefficient.